Questionnaire Analysis on Incidence and Risk Factors of Dry Eye in Children From a Myopia Outpatient Clinic - Wang, Ning; Zhuang, XiaoYun; Zhong, XiaoWei; Zhang, Ju; Li, GuangWei; Li, Suxia (Frontiers in Medicine, 2022)
Objective To analyze the incidence and risk factors of dry eye in children from a myopia outpatient clinic via a questionnaire and Keratograph 5M. Methods A cross–sectional study was performed. sThere were 214 children (428 eyes) selected from the myopia outpatient clinic of the affiliated Eye Hospital of Shandong First Medical University from July 2021 to September 2021, including 105 boys (210 eyes) and 109 girls (218 eyes), with an average age of 10.1 ± 2.5 years. The incidence rate and influence factors for dry eye were calculated. Results Thirty–four of 214 children were diagnosed with dry eye, accounting for 15.9% of the patients. The correlation between fussy eating and the tear meniscus height was statistically significant (Z = −2.158, p = 0.039), along with the correlation between short–distance use of eyes and the tear meniscus height (Z = −2.135, p = 0.033). The degree of meibomian gland deficiency was graded. The meibomian gland was graded as grade 1 in 242 eyes (68.9%), grade 2 in 104 eyes (29.6%), and grade 3 in 5 eyes (1.4%). There was a significant difference in the correlation between eye rubbing and the incidence of dry eye in children (Z = −2.747, p = 0.008). There was also a significant difference in the correlation between picky eating and the incidence of dry eye in children (Z = −2.347; p = 0.024). There was a statistically significant correlation between the time of looking at electronic products and the morphology of the meibomian gland (Z = −2.201, p = 0.028). The results showed that the effect of mild and moderate ametropia on the non–invasive tear breakup time in children was statistically significant (Z = −2.027; p = 0.043). Conclusion There is a high incidence of dry eye in children in the myopia outpatient clinic. There is a significant correlation between picky eating, eye rubbing, and the incidence of dry eye. Looking at electronic products for a long time will also affect the morphology of the meibomian gland in children.